Failure of Good Governance At the Local Level: A Case Study of PKH Social Assistance and Village Fund Management - Rahman, Ikhwan; Karim, Amirul; Masrial, Masrial; Syamsudin, Syamsudin (Khalaqa: Journal of Education and Learning, 2025)
Good governance is a fundamental prerequisite for creating effective, transparent, accountable, and responsive governance to public needs. However, the reality on the ground indicates that governance practices are not aligned with these principles of good governance. Implementation failures are still common, especially at the lowest levels of government, such as villages. This phenomenon is reflected in various problems, ranging from the ineffective distribution of social assistance, weak oversight mechanisms for the use of village funds, to minimal active community participation in decision-making and oversight processes. The consequences of implementation failures of good governance. This is a drastic decline in public trust in government institutions and has hampered the achievement of development program goals. This article comprehensively analyzes the root causes of governance problems at the village level, emphasizing the importance of internalizing and implementing the principles of transparency, accountability, participation, and law enforcement as key pillars for building a cleaner, more responsive, and more welfare-oriented government. Furthermore, this study identifies and proposes a series of holistic improvement solutions, based on an inclusive, participatory approach and optimizing the use of information technology, to improve the quality and effectiveness of public services at the village level.